The value and effectiveness of geriatric assessments for older adults with cancer: an umbrella review - Sharon He; Heather L. Shepherd; Meera Agar; Joanne Shaw (BMC Geriatrics)
Abstract Purpose This umbrella review aimed to summarise and synthesize the evidence on the outcomes reported and used to assess the value and or efficacy of geriatric assessments (GAs) for older adults with cancer. Methods Six electronic databases, PsycINFO, MEDLINE, Embase, CINAHL, Cochrane Library and Web of Science databases, were searched to identify systematic reviews with or without meta-analyses that described the value or outcomes of GAs for older adults with cancer. Results Twenty-six systematic reviews were included, of which six included a meta-analysis of the data. Thirteen associations and or outcomes were identified. Overall geriatric impairments predicted or were associated with majority of identified outcomes. However, the type of domains associated with outcomes differed within and across reviews. Only treatment toxicity was statistically significantly lower for patients allocated to the GA intervention group compared to standard care. Systematic reviews without meta-analyses demonstrated a positive impact of GA with management on treatment completion, communication and care planning and patient satisfaction with care. Conclusion There is evidence demonstrating the predictive value of GAs for older adults with cancer. GAs seems to be beneficial for older adults with cancer across some outcomes, with strong evidence demonstrating the impact of GA with management for treatment toxicity. However, there is mixed or limited evidence demonstrating the effect of GA in other treatment modalities, and on quality of life and economic outcomes.